Curricula and their effectiveness in understanding comedy for directing students of the college of Fine Arts, University of Basrah: comedy performances as an example - Nour Sabah Abdul Muttalib; Hala Hassan Sabti (Basrah Arts Journal, 2023)
The applications lesson is a bud that is subject to several intellectual and technical limitations, which are supervised by specialized professors, a space that gives the student a space of freedom in choosing texts and representative students, and opens a wide field for applications students to express their technical and methodological inclinations, whether by adopting a specific direction or trying to diverge and be creative. Therefore, we find that the personality of the student in the study of applications has its impact and existence through his adoption and choice of theatrical work as a text and treatment. Artistic and cultural institutions. the research was directed to demonstrate the effectiveness of the curricula in understanding comedy for directing students of the Faculty of Fine Arts.